ETHNOBOTANY OF MEDICINAL PLANTS USED BY THE LOCAL COMMUNITY AT THE FOOT OF THE MOUNT UYELEWUN, EAST NUSA TENGGARA - Elly Purwanti; Yuni Pantiwati; Endrik Nurrohman; Astika Dwi Lorosae (PROGRAM STUDI PENDIDIKAN BIOLOGI FAKULTAS KEGURUAN DAN ILMU PENDIDIKAN UNIVERSITAS JEMBER, 2023)
This study aims to explore and identify the medicinal plants used by the Uyelewun local community. It encompasses plant species, multi-aspect utilization, processing methods and how to use, and their medical benefits to heal diseases. This descriptive exploratory study was conducted in May 2019 in six villages, namely Panama Village, Meluwiting Village, Loyobohor Village, Leudanung Village, Balauring Village, and Wairiang Village. These six villages were categorized into three groups: 1) modern village, 2) developing village, and 3) traditional village. Seventy-eight respondents, comprising local villagers, traditional healers, and adat leaders/elders, were selected using purposive and snowball sampling techniques. This study was performed in four stages, viz. 1) survey of research locations and selection of respondents, 2) semi-structured interviews, 3) plant documentation, and 4) plant inventory. The data obtained were then analyzed descriptively using percentages, averages, and content analysis. The results showed that 1) the local community used 82 plant species from 40 families as medicinal plants; 2) the traditional villages had the highest number of medicinal plants (43%), and the modern villages had the highest number of plant species (64%); 3) most plant habit was trees (43%); 4) the majority of plant was from uncultivated/wild plant (55%), obtained mostly from the surrounding environment (55%) and rarely from the beach (2%); and 5) the most consumed part of the medicinal plants was fruits (70%).